(untitled) (Nigerian Journal of Technology, 2017)
The characterization of some clay as refractory materials for furnace lining has become relevant to find solutions to the cost involved in the purchase and importation of these refractory materials. This work investigated the refractory properties of clay samples for their suitability for use in the industries. Clay samples were collected from Gakem and Abouchiche areas and analysed for physical and chemical properties to determine the suitability of the clays as refractory materials. The results showed cold crushing strength (21.46MN/m2), thermal shock resistance (27 cycles), bulk density (3.52g/cm3), linear shrinkage(3.80%), apparent porosity (28.84%) and permeability (80%) for Gakem; and cold cold crushing strength (18.40MN/m2), thermal shock resistance (25 cycles), bulk density(2.81g/cm3), linear shrinkage (3.70%), apparent porosity (25.86%) and permeability (77%) for Abouchiche respectively. The chemical compositions of these clay samples were also investigated. The results showed that the samples fall under Aluminosilicate type of clay because of their high values of Aluminium Oxide and Silicon Oxide. Tests showed that clay from these areas can be used to produce refractory materials that can withstand a furnace temperature of about 1600°C. http://dx.doi.org/10.4314/njt.v36i3.26